THE SEMANTIC UNITY LOVE–INDIFFERENCE–HATE: THE MEANINGFUL COMPONENT - Yu. V. Demicheva (Гуманитарные и юридические исследования)
The article examines the significant component of the semantic unity «love–indifference–hate», understood as a multilevel mental formation that lies in consciousness, language and culture. The relevance of the study is due to the important role of the concepts «love», «indifference», «hatred», acting as fundamental life guidelines of a person. The research is carried out on the material of modern defining dictionaries of the Russian language. This semantic unity contains both the semantic opposition of love and hate, and the opposition of these components and the «neutral point» – indifference. The immediate subject of research is the lexical and phraseological units of the Russian language, in meanings of which lexemes referring to the corresponding components of the semantic unity, are present. For each of the three components of the semantic unity, an assessment is made of the lexical and phraseological means of their expression, presented in the defining dictionaries. The study of this semantic unity is carried out for the first time. A conclusion is made about their asymmetry: love absolutely dominates in terms of the number of units expressing its semantics; indifference and hatred in this respect turn out to be comparable. It has been determined that nouns that concretize the object of the corresponding feeling are found in both love and hatred, but absent in indifference. Also, indifference lacks the ways of lexical expression using suffixoids, which are present in love and hate. It was revealed that the logicalsemantic oppositions of the components of the semantic unity are manifested in the lexical system of the language: it contains both the opposition love – hate and the opposition indifference – love, but there is no opposition hate – indifference.